Post-vaccination immunity phenotypes upon usage of EpiVacCorona vaccine in the persons who suffered COVID-19 - L. P. Sizyakina; I. I. Andrreeva; M. V. Kharitonova; N. S. Zaitseva; D. S. Lyubimov; V. Ya. Zakurskaya; A. А. Totolian (Медицинская иммунология)
The dominance of reliably immunized population is a fundamental factor in prevention of COVID-19 pandemia, with immune prophylaxis taking a dominant position. Due to lack of clear data on the intensity of specific immunity after a new coronavirus infection, consolidation of immunological memory by vaccination becomes the urgent task, in order to exclude the risk of re-involvement of previously ill patients into the epidemic process. Meanwhile, many questions related to vaccination of COVID-19 survivors do not get distinct answers. To study the features of immune response, using a vaccine based on SARS-CoV-2 peptide antigens (EpiVacCorona), we monitored 81 participants. The inclusion criteria were data confirming COVID-19 in the anamnesis (medical documentation), low levels or absence of antibodies to the SARS-CoV-2 nucleocapsid protein, and negative PCR tests for SARS-CoV-2. When assessing the data of post-vaccinal immunity checked 21 days after 1st dose of the vaccine, the patients were divided into 2 groups: those who did not respond, and those who developed the immune response. In order to identify possible reasons for different phenotypic patterns of humoral response to vaccination, a comparative analysis of B lymphocyte indexes was carried out in these groups. Absolute counts, subpopulation composition and activation potential of peripheral blood B lymphocytes were determined by flow cytofluorometry using appropriate labeled monoclonal antibodies purchased from Beсkman Coulter. Comparative analysis of B lymphocyte indexes on the day of first vaccination showed that the persons who did not respond to the vaccine had smaller counts of circulating B cells, i.e., both percentage and absolute cell numbers, than in comparison group, as well as changed ratio of B1-to-B2 subpopulations. After administration of the first vaccine dose (by day +21), in alternative variant of the antibody response to V1, the differences in the parameters of B cells were presented as a smaller percentage and absolute numbers of regulatory B lymphocytes in non-responding participants. Moreover, the contents of minor B cell subpopulations were decreased in the non-responding group than in the comparison group, thus affecting the values of the B1:B2 ratio. In general, the presented data demonstrate that the absence of secondary immune response to antigens of the SARS-CoV-2 peptide vaccine could be is associated with altered differentiation of B1 and B2 subpopulations, B regulatory lymphocytes, B memory cells.